PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP BERPIKIR KRITIS SISWA KELAS IV PADA PEMBELAJARAN BAHASA INDONESIA - Mochammad Aprieyadi Phermadi; Lutfi; Fitria Rosmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore how the Learning Cycle 5E model can enhance elementary students’ critical thinking skills in Indonesian language learning. The research used a quantitative approach with an experimental design of Posttest Only Control Group. The subjects were 60 fourth-grade students from SDN Pondok Labu 02 Jakarta Selatan, divided into an experimental group and a control group. The instrument used was a critical thinking test consisting of four indicators: interpretation, analysis, evaluation, and inference. The results showed that the experimental group achieved an average posttest score of 85.09%, while the control group scored 67.50%. The t-test result (tcount = 5.450 > ttable = 1.325, sig = 0.000 < 0.05) indicated a significant effect of the Learning Cycle 5E model. The R Square value of 0.507 suggests that the model contributed about 50.7% to the improvement in students’ critical thinking skills. In conclusion, applying the Learning Cycle 5E model effectively supports students in developing critical and active thinking during Indonesian language learning.